Fundamentals of Biomechanics - Knudson, Duane (Springer, 2007)
This second edition of Fundamentals of Biomechanics was developed primarily to update a well-received text. The uniqueness of integrating biological and mechanical bases in analyzing and improving human movement has been expanded with more examples, figures, and lab activities. Citations to the latest research and web links help students access primary sources. Students and instructors will appreciate the CD with lab activities, answers to review questions, sample questions, and graphics files of the illustrations.
Keywords: BIOMECHANICS